Green cosmeceuticals: design and evaluation of environmentally-friendly sunscreens with Vaccinium varingiaefolium leaf bioactives - Kosasih Kosasih; Ana Yulyana; Cynthia Dewi (Pharmacia)
Aim: The increasing consumer demand for safer, eco-friendly sunscreens has propelled research toward natural, plant-based ingredients with photoprotective properties. This study aimed to assess the sun protection factor (SPF) of Vaccinium varingiaefolium (Cantigi) leaf extracts, extract-loaded gelatin nanoparticles, and gel formulations containing either the extract (F1) or the nanoparticles (F2). Method: The leaves were extracted using 70% ethanol, and the resulting extract was characterized and further processed into gelatin-based nanoparticles through the desolvation method. Result: The nanoparticles exhibited a size of 174.7 ± 0.26 nm, a PDI of 0.337 ± 0.05, a zeta potential of 2.82 ± 0.39 mV, and an entrapment efficiency of 38.66 ± 0.15%. The extract, nanoparticles, and their respective gel formulations (F1 with extract, F2 with nanoparticles) were evaluated for SPF and stability under accelerated conditions. The extract demonstrated the highest SPF value (30.48), providing 97% UVB protection, followed by nanoparticles (28.48), gel F1 (21.56), and gel F2 (16.10), which offered 93–96% UV blockage. Conclusion: These findings underscore the potential of Cantigi as a natural sunscreen agent, particularly in its crude extract form. While the current formulations offer moderate protection suitable for daily use, further optimization is necessary to achieve higher SPF benchmarks for extended outdoor exposure. This study advocates for the incorporation of Cantigi leaf bioactives into sustainable sunscreen products.